A systematic review of experimental evidence for antiviral effects of ivermectin and an in silico analysis of ivermectin's possible mode of action against SARS‐CoV‐2. (28th January 2021) - Kinobe, Robert T.; Owens, Leigh
Abstract: Viral infections remain a major cause of economic loss with an unmet need for novel therapeutic agents. Ivermectin is a putative antiviral compound; the proposed mechanism is the inhibition of nuclear translocation of viral proteins, facilitated by mammalian host importins, a necessary process for propagation of infections. We systematically reviewed the evidence for the applicability of ivermectin against viral infections including SARS‐CoV‐2 regarding efficacy, mechanisms and selective toxicity. The SARS‐CoV‐2 genome was mined to determine potential nuclear location signals for ivermectin and meta‐analyses for in vivo studies included all comparators over time, dose range and viral replication in multiple organs. Ivermectin inhibited the replication of many viruses including those in Flaviviridae, Circoviridae and Coronaviridae families in vitro . Real and mock nuclear location signals were identified in SARS‐CoV‐2, a potential target for ivermectin and predicting a sequestration bait for importin β, stopping infected cells from reaching a virus‐resistant state. While pharmacokinetic evaluations indicate that ivermectin could be toxic if applied based on in vitro studies, inhibition of viral replication in vivo was shown for Porcine circovirus in piglets and Suid herpesvirus in mice. Overall standardized mean differences and 95% confidence intervals for ivermectin versus controls were −4.43 (−5.81, −3.04), p  < 0.00001. Based on current results, the potential for repurposing ivermectin as an antiviral agent is promising. However, further work is needed to reconcile in vitro studies with clinical efficacy. Developing ivermectin as an additional antiviral agent should be pursued with an emphasis on pre‐clinical trials in validated models of infection.